First molecular characterisation and expression analysis of a teleost thioredoxin-interacting protein (TXNIP) gene from rock bream (Oplegnathus fasciatus). Issue 1 (September 2015) - Kim, Ju-Won; Lee, Jung-Ho; Bae, Jin-Sol; An, Cheul Min; Nam, Bo-Hye; Jeong, Ji-Min; Park, Chan-il
Highlights Thioredoxin-interacting protein cDNA was identified from a rock bream. RbTXNIP had a well-conserved arrestin domain within the aligned sequence. RbTXNIP gene was predominantly in the RBC, intestine, and spleen. RbTXNIP was up-regulated after recombinant TRx1 protein injection. RbTXNIP was down-regulated in the fish infected with several pathogens.